Non-Jewish volunteers in the Kibbutz Movement and the establishment of state conversion in Israel in the 1970s. Issue 5 (3rd September 2017) - Fisher, Netanel
Abstract: This article reveals how non-Jewish volunteers who joined kibbutzim in Israel in the early 1970s created a situation that brought about the establishment of an Israeli state conversion system. Contrary to the prevailing idea that issues related to non-Jewish immigrants and conversion became practical and urgent only from the 1990s on, the central argument in this article is that a structured conversion system had already been established 20 years earlier, as a result of the unique collaboration between the secular Kibbutz Movement and Chief Rabbi Shlomo Goren, who assisted non-Jewish volunteers to convert to Judaism. This collaboration proves the ability of religious and secular to cooperate in order to promote the preservation of Israel's Jewish character, but also points out the difficulties involved in doing so, which reflect the tensions that still exist between religion and secularism in Israel.